Succinyl-carrageenan on a localised surface plasmon resonance fiber sensor for ammonium ion assays - Abu Bakar, Mohd Hafiz; Azeman, Nur Hidayah; Mobarak, Nadhratun Naiim; Nazri, Nur Afifah Ahmad; Sulaiman, Rozita; Arsad, Norhana; Mahdi, Mohd Adzir; A Bakar, Ahmad Ashrif (Royal Society of Chemistry (RSC), 2022)
This paper reports on the development of a highly sensitive and selective NH4+ tapered fiber optic Localized Surface Plasmon Resonance sensor (LSPR) coated with succinyl-carrageenan as the sensing material. The tapered fiber optic was coated with silver nanoparticles (AgNP) and succinyl-carrageenan. A FESEM study reveals that the AgNP-succinyl-carrageenan-coated LSPR fiber probe has a wavelike topology. An AFM study reveals that the AgNP-succinyl-carrageenan-coated LSPR fiber probe was nearly 2 times rougher than AgNP-carrageenan, showing an increase in the density of the electronegative atom oxygen as compared to the carrageenan. The sensitivity of the AgNP-succinyl-carrageenan-coated LSPR fiber optic sensor toward NH4+ detection was 3.20 nm ppm−1. The LOD and LOQ of the AgNP-succinyl-carrageenan-coated LSPR fiber sensor were 0.48 and 1.44 ppm, respectively, lower than its pristine form. The detection range of the developed sensor was broader compared to its pristine form ranging between 0.5-3.0 ppm. The fabricated sensor was highly selective towards NH4+ and showed a good correlation when validated with the standard method with the value of R2 = 0.973. The AgNP-succinyl-carrageenan-coated LSPR fiber sensor has a wider detection range than the standard method indophenol reagent with the advantages of simple, safe, highly selective, and in situ detection.